ANALISIS PUTUSAN LARANGAN EKSPOR BIJIH NIKEL INDONESIA YANG DIGUGAT UNI EROPA DI WORLD TRADE ORGANIZATION - NIM. A1011201089, FIKRI FARYANSYAH (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractThe WTO and GATT play a role in regulating international trade and as mediators in disputes that occur between the two parties accompanied by valid and relevant evidence with other international provisions for a country in dispute.In the World Trade Organization Dispute Settlement decision no. 592 between Indonesia and the European Union regarding the policy of prohibiting nickel ore exports based on Minister of Energy and Mineral Resources Regulation No. 11 of 2019 and Law No. 3 of 2020 regarding the cessation of exports of Nickel ore and other raw minerals which according to the World Trade Organization's Dispute Settlement violates Article XI.1 GATT and is not justified by Articles XI.2 GATT and XX d GATT.Regulations prohibiting nickel ore exports by Indonesia with Article XI.1 GATT according to the European Union it violates because it hampers export freedom, eventhough there are several countries that have much more nickel production than Indonesia, which is around 11 percent according to the 2021 Nickel Institute data. In terms of the decision of Panel DS 592 R Indonesia with a policy of prohibiting the export of Nickel ore through Minister of Energy and Mineral Resources Regulation No. 11 of 2019 in order to maintain supply stability which makes a deviation from the principles of Non-Discrimination and Most Favoured Nation (MFN) by the WTO and GATT Dispute Settlement.Keywords: WTO Dispute Settlement, GATT, Nickel ore exports, European Union lawsuit. AbstrakWTO dan GATT berperan dalam mengatur perdagangan internasional serta sebagai penengah dalam sengketa yang terjadi antara kedua pihak yang disertai dengan bukti valid dan relevan dengan ketentuan internasional lainnya terhadap suatu negara yang bersengketa.Pada putusan Dispute Settlement World Trade Organization No. 592 antara Indonesia dengan Uni Eropa terkait kebijakan larangan ekspor bijih Nikel berdasarkan Peraturan Menteri ESDM No. 11 tahun 2019 dan Undang-undang No. 3 tahun 2020 berkenaan dengan penghentian ekspor bijih Nikel dan mineral mentah lainnya yang menurut Dispute Settlement World Trade Organization melanggar Pasal XI.1 GATT serta tidak di justifikasi dengan Pasal XI.2 GATT dan XX d GATT.Regulasi larangan ekspor bijih Nikel oleh Indonesia dengan ketentuan Pasal XI.1 GATT menurut Uni Eropa melanggar karena menghambat kebebasan ekspor, padahal ada beberapa negara yang memiliki produksi Nikel yang jauh lebih banyak dari Indonesia yang sekitar 11 persen menurut Data Nickel Institute 2021. Dari sisi putusan Panel DS 592 R Indonesia dengan kebijakan larangan ekspor bijih Nikel melalui Peraturan Menteri ESDM No. 11 tahun 2019 demi menjaga kestabilan pasokannya yang membuat penyimpangan terhadap prinsip Non Diskriminasi dan Most Favoured Nation (MFN) oleh Dispute Settlement WTO dan GATT.Kata Kunci : Dispute Settlement WTO, GATT, ekspor bijih Nikel, gugatan Uni Eropa.